Annual Assessment of Noise Generated by Road Traffic using Measurements. (2017) - Jagniatinskis, Aleksandras; Fiks, Boris; Zaporozhets, Oleksandr; Mickaitis, Marius
Abstract: The noise produced by road transport by the World Health Organization contributes basically to the environment noise pollution. The environmental noise impact by the DIRECTIVE 2002/49/EC is described using the one year average noise descriptors L den, L night which usually is presented via the appropriate noise maps. However, there are cases when together with the calculation model the direct acoustic measurements are needed. The permanent noise monitoring for this purpose often is unpractical and a short-term noise level measurements become important. When long-term noise measurement (annual noise monitoring) is not applicable, the standard ISO 1996-2 allows carry out measurements in shorter time intervals than the specified one. For the case of the suburbia roads it is shown that exist the possibility to assess the one year descriptors using the data coupled from the few hours' measurements only. As shown in paper it based on the statistics of traffic flow data for heavy and light transport (intensity, speed) as well as on the measured statistics of sound exposure levels of vehicle passing bys. For the urban traffic noise, as was shown by the statistical analysis of one year experimental data, at least one whole-day measurements are needed. In both cases chosen short-term interval or chosen whole-day must satisfy so-called representative measurement conditions.